(untitled) (Global Journal of Human-Social Science, 2021)
LGBTphobia, school violence and the consequences of this violence on access and permanence to education for this population. The school is the locus of subject production, being one of the main spaces for subjectivation and self-expression and its social dialogue. This study can be circumscribed in a literature review research, having as method a systematic review research. Ten scientific articles found on the SCIELO and PEPSIC platform were analyzed. The results indicate specific forms of violence in the regulation of gender and sexuality dissidences, being structurally incited and produced in public spaces, having as a guideline a sexuality and a gender to be followed, in a special regime, called heteronormativity. The materiality of these types of violence takes place through psychological, physical, structural and sexual violence. Thus, the need for these productions that question heteronormativity in the school environment is evident, considering the socio-historical exclusion of the LGBT community and its non-insertion in school spaces, as well as the production and implementation of public policies to minimize the effects of these violences.